The antibiogram: key considerations for its development and utilization. Issue 2 (25th May 2021) - Truong, William R; Hidayat, Levita; Bolaris, Michael A; Nguyen, Lee; Yamaki, Jason
Abstract : The antibiogram is an essential resource for institutions to track changes in antimicrobial resistance and to guide empirical antimicrobial therapy. In this Viewpoint, data and examples from literature are presented that suggest institutions have not completely adopted the standardized approach in developing antibiograms, as variations in the development methodologies of antibiograms exist despite consensus guidelines (M39) published by CLSI. We emphasize developing antibiograms in line with the M39 recommendations will help ensure that they are accurate, reliable and valid, and highlight that understanding the limitations of antibiogram data is critical to ensuring appropriate interpretation and application to clinical decision-making. We also stress the importance of easy accessibility and education on antibiogram use, to allow for prescribers to select the most optimal empirical treatment regimens and propose the creation of an abbreviated antibiogram for frontline users. Multidisciplinary antimicrobial stewardship programmes are vital to accomplishing these goals.